Efficacy of Probiotic Supplementation for Preventing Pediatric Urinary Tract Infections: A GRADE‐Based Dose–Response Meta‐Analysis - Sayed Yousef Mojtahedi; Masoumeh Ghasempour; Maryam Ghodsi; Paniz Pourpashang (Health Science Reports, 2026)
ABSTRACT Background and Aims Probiotic supplementation has been proposed as a non‐antibiotic strategy for preventing urinary tract infections (UTIs) in children, but its efficacy remains uncertain. We evaluated the effects of probiotic supplementation on pediatric UTI incidence or recurrence, explored potential dose–response relationships, and assessed the certainty of the evidence using GRADE. Methods This systematic review and meta‐analysis followed PRISMA 2020. Electronic databases were searched from January 1, 1990, through June 5, 2025, without language restrictions. Thirteen randomized controlled trials involving 3129 participants were included. Risk ratios (RRs) with 95% confidence intervals (CIs) were pooled using a random‐effects model. Subgroup and dose–response analyses were exploratory, and certainty of evidence was evaluated using GRADE. Results Probiotic supplementation was associated with a modest reduction in the overall risk of UTI incidence or recurrence (RR = 0.93, 95% CI: 0.88–0.99; p = 0.02), with substantial heterogeneity ( I 2 = 71.1%). For UTI incidence, the pooled estimate was RR = 0.95 (95% CI: 0.89–1.01; p = 0.12); for UTI recurrence, it was RR = 0.89 (95% CI: 0.81–0.99; p = 0.03). No statistically significant nonlinear dose–response association was identified (P for nonlinearity = 0.15). Funnel‐plot asymmetry was visually apparent, but Egger's regression test ( p = 0.21) and Begg's rank‐correlation test ( p = 0.45) did not provide statistically significant evidence of small‐study effects. Certainty of evidence was low because of risk‐of‐bias and inconsistency concerns. Conclusion Probiotic supplementation may be associated with a small reduction in pediatric UTI risk, but substantial clinical and statistical heterogeneity and low‐certainty evidence limit confidence in the pooled estimate. The apparent association with lower UTI recurrence should be interpreted cautiously, and the evidence does not establish an optimal probiotic dose or equivalent efficacy across strains and formulations.